Displacement and speed characteristics of the breaststroke turn - A cinematorgraphic analysis - Huellhorst, U.; Ungerechts, B. E.; Willimczik, K. (Swimming Science V, 1988)
The amount of time spent in turning in swimming events, especially in long-distance races, is astonishingly high. Thayer and Hay (1984) found that, for example, 39% of the total race time in the 200-m breaststroke event was spent on turning. They used short-time measurement to record the time for the whole turning phase including the approach, the turn, and the glide. Quite a few previous investigations used different distances before and after the actual turn (Fox, Barthels, & Bowers, 1963; Scharf & King, 1964). Most of these investigations, however, intended to compare different turning techniques. Chow, Hay, Wilson, and Imel (1984) were the first who did not take arbitrary distances to the wall (distancein, distance-out) as a basis of their measurements. With the help of highspeed films they determined both distances for each swimmer individually according to the cycles of swimming. Distance-in was defined as the horizontal distance between the vertex of the head of the swimmer and the wall at the beginning of the last stroke before initiating the turn; distance-out was defined as the distance from the wall to the end of the first stroke after the turn. From these distances they computed the time for the two subphases of the turn and the total time for turning. Up to the present, none of the investigations referred to the center of gravity (cg) and consequently no continuous curves of the displacement and speed of the cg exist. The aim of this study was to make a differentiated analysis of the breaststroke turn on the basis of displacement and speed curves of the center of gravity.